(untitled) - Wolfe, Gerard R. (New York, 2004)
Twelve well-mapped walking tours help you discover a city with a long history of being on the forefront of architectural innovation. These tours highlight the works of architectural giants including Frank Lloyd Wright, Dankmar Adler, Louis Sullivan, and others who helped revamp the American skyline.
Keywords: Architecture,Chicago (Ill.),Kiến trúc,Chicago; Buildings, structures,Xây dựng; Illinois,Chicago,Illinois,Chicago